Solve a-2b+c=-6, a+5c=-12, -a+6b+4c=3 by Substitution

preview_player
Показать описание
Solve a-2b+c=-6, a+5c=-12, -a+6b+4c=3 by substitution. We learn how to solve a-2b+c=-6, a+5c=-12, -a+6b+4c=3 by substitution which is on the topic of Solving Systems of Three Equations w/ Substitution with this free online math video lesson. This video uses the substitution method to solve a system of three equations. We show you step by step how to solve each system by substitution of three equations. #systemsofthreeequations #substitution #minutemath

Every Month we have a new GIVEAWAY that is FREE to Enter. See link below for details. You can enter Every Month!

Visit our website for links to all of our videos:

Need a Math Tutor?

Great Educational Resources Here:

Nominate a Great Teacher Here:

Have Math Lesson you would like to add to our community of videos? Click here:

Check out our Finance, Business and Life YouTube Channel:

Consider supporting us on Patreon...

Follow us for...
Рекомендации по теме